Characteristics of runoff changes and their climatic factors in two different glacier-fed basins - Sun Zhenqi; Wang Shijin; Li Zhongqin (Arctic, Antarctic, and Alpine Research)
The hydrological regulation function of glaciers in different watersheds is different. This study took the Yanggong River Basin (YRB) and Urumqi River Basin (URB) as two typical cases, to explore the runoff change differences and their responses to climate factors from 1979 to 2017. In the past 39 years, the YRB’s annual runoff showed an insignificant trend of increasing first and then decreasing, while the URB’s increasing trend was significant. From the 1980s to the 2010s, the YRB’s monthly runoff extremum occurred earlier than before, and the peak value decreased. The time of monthly runoff extremum in the URB has not changed, but the peak value is increasing. Both basins experienced an increase in annual temperatures from 1979 to 2017, with the rate of warming being more pronounced in the URB. The precipitation in the YRB had no significant trend from 1979 to 2017, and the significant increasing trend in annual precipitation extended in the URB from 1998 to 2010. The YRB’s runoff change was mainly influenced by the flood season precipitation, while the URB’s runoff increase was due to the temperature rise causing faster glacier and snow melt, and the summer precipitation change. In continental glacier basins with many glaciers, the regulation function of glaciers on total runoff is more significant.